Application of the phasor measurement unit for protecting unintentional islanding of the distribution system - Arefin, A.A. (Elsevier, 2023)
Power networks currently make substantial use of phasor measurement units (PMU) due to the ability to enhance system reliability. PMUs can produce data on system frequency, angle, voltage, and current magnitude. A broadly applied algorithm using the discrete Fourier transform has been suggested for determining PMU. PMUs guarantee grid observability, which unquestionably upholds the stability of the power network; however, the main problems with PMUs include noise stuffing, design, signal channeling, and other complicated elements, like on-site data quality. Missing PMU data are recovered using polynomial interpolation. Lagrange interpolation is also used to assess data quality and locate PMU data that are missing. PMU is a monitoring tool that assesses frequency, voltage/current angle, and magnitude. Universally synchronized data from PMU are discovered and analyzed to improve the transmission and distribution sideâs dependability. PMUs can handle magnitude and phasors simultaneously, which is why they are also known as synchro-phasor devices. Â© 2024 Elsevier Inc. All rights reserved.